JERU (JERMAN SERU): Development of Interactive Educational Website to Improve German Language Mastery Through Fun and Effective Approach - Anisa Tri Saraswati; Bukhori, Herri Akhmad; Aulia Az-Zahra; Kayla Amaturrahman; Syaula Qonit Helga (Nexus Publishing NXP, 2024)
The development of language learning websites in the current era is increasing rapidly. The purpose of this research is to produce learning media based on German language learning (JERU) websites for students and beginners. Our website development is based on the difficulties experienced by students at school in learning early German learning materials. This learning media emphasizes on effective, efficient, and fun methods applied through the website by providing various interactive games according to the level of material that has been learned and can be accessed easily. Adjustments to the use of multimedia, interactivity, and content can be adjusted to individual needs. The utilization of technology in the development of German language learning websites has great potential to increase learner motivation, engagement, and learning outcomes. However, the development of media such as combining technology into an appropriate curriculum still needs further consideration. The role of technology, especially websites, in German language learning should be further explored. Through the website, it can provide a broad overview and a very effective solution when developing innovative, responsive, and fun language learning methods to current developments.